Question of the Meaning of Constitution in Husserlean Phenomenology - Silva Gálvez, Nicolás (Resonancias. Revista de Filosofía, 2022)
The present research exposes and problematizes the notion of “constitution” in the framework of Edmund Husserl’s phenomenology. This concept is understood, broadly speaking, as the donation of sense that consciousness grants to phenomena. Thus, constitution acts as an indispensable process to organize the analysis of the diverse elements of the phenomenon, in order to establish its meaning in a synthesis. However, its very conception is not fully elucidated in the work of the Moravian thinker. That is to say, I think that the very constitution of the constitution remains in the shadows: it is not made clear what the original meaning of the process of constitution is, that is, it is not determined what the constitution of phenomena is. In order to clarify this problem, I examine its reference in two moments of Husserlean work and I rely on certain arguments of the philosopher Roman Ingarden.